IMAGE BASED STUDENT CERTIFICATE DATA SEARCH SOFTWARE USING OCR METHOD CASE STUDY AT SMP PASUNDAN 1 BANDUNG - Hadikaryana, Oscar (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
OCR (Optical Character Recognition) is an effective solution for converting printed documents to digital documents. The problem that arises in the process of recognizing computer documents is how the recognition technology is to identify various types of characters with various sizes and shapes. The introduction method used in this final project is the Template Matching Correlation method. Before the recognition process, the input image with the format bitmap or jpg* is processed first in the preprocessing process, which includes binarization, segmentation, and image normalization. The average recognition success rate generated by this system is 92.40%. The final results show that the use of the Template Matching Correlation method is sufficient to build an OCR system with good accuracy effectively.